ANALISIS PENYEBAB KETERLAMBATAN PEKERJAAN REPLATING LAMBUNG PADA PROYEK KAPAL X MENGGUNAKAN METODE FAULT TREE ANALYSIS - Triwardani, Agil; Dewi, Sinta (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
The The success of a project is marked by the achievement of the planned target. However, in its implementation, delays often occur, including in the hull replating work. In the ship repair project X at PT XYZ, this work experienced a schedule delay due to constraints on materials/equipment, labor, and management. The purpose of this study was to determine the root cause of the delay and propose improvements. The analysis was carried out using the Fault Tree Analysis (FTA) method to identify the root cause of the delay, while the improvement proposal was carried out using the Kaizen 5S method (Seiri, Seiton, Seiso, Seiketsu, Shitsuke). Based on the results of the analysis using the FTA method, the main factor causing the delay was the material/equipment factor with a probability value of 0.304. This factor includes three main indicators of the cause of the delay, namely the delay in the arrival of materials, the ordered materials are not appropriate, and the lack of adequate equipment. The application of the Kaizen 5S method aims to improve work efficiency through better material/equipment management and creating an organized work environment. Thus, it is hoped that the application of both methods can reduce delays and prevent similar problems in the future.